IMPLEMENTASI KEBIJAKAN PENGELOLAAN PEMBANGUNAN DAERAH TERTINGGAL TERDEPAN TERLUAR (3T) DI PULAU MARAMPIT KECAMATAN NANUSA KABUPATEN KEPULAUAN TALAUD - DIRANGGA, EFIPANIA; LENGKONG, FLORENCE; KOLONDAM, HELLY (Sam Ratulangi University, 2021)
Marampit island is aborder area between countries and is included in the category ofunderdeveloped, frontier, outermost (3T) aeras since 2017. The problems experienced by Marampitisland in terms of development, economy, social, education, health, and policy implementers do notrespond to complaints and suggestions from the government and the community on Marampitisland. This study discusses how to implement development management policies forunderdeveloped, frontier, outermost (3T) areas on Marampit island, Nanusa District, TalaudIslands Regency. Through the use of descriptive qualitative research methods, with the datasources used in this study, namely primary and secondary data and data collection techniques werecarried out by observation, interviewes and documentation. With as many as 8 informants. Thefocus of this study uses the theory of Charles Van Meter and Donald Van Horn where the succes ofpolicy implementation is influenced by several indicators, namely :Policy standars andobjectives/policy measures and objectives, resouces, characteristics of implementing organizations,communication between related organizations and implementation activities, disposition or attitudeof implementers, social, economic, political environment. The results show that the process ofimplementing development management policies on Marampit island as an underdeveloped,frontier, outermost (3T) area still has lot of overlap between sectors and intitutions as well as thelack of coordination due to sectoral egos and different priorities of policy implementers, as well aslimited health, education, and information and communication infrastructure,thus requiring specialattention from the government.Keywords : Policy Implementation, Development, Underdeveloped Frontier Outermost Areas